Radiogenic and stable Sr isotope ratios (87Sr/86Sr, δ88/86Sr) as tracers of riverine cation sources and biogeochemical cycling in the Milford Sound region of Fiordland, New Zealand. (15th January 2016) - Andrews, M. Grace; Jacobson, Andrew D.; Lehn, Gregory O.; Horton, Travis W.; Craw, Dave
Abstract: This study reports radiogenic Sr isotope ratios ( 87 Sr/ 86 Sr), stable Sr isotope ratios (δ 88/86 Sr), and major ion concentrations for river, rock, sediment, soil, and plant samples collected from the Cleddau and Hollyford catchments in the Milford Sound region of Fiordland, New Zealand. The catchments primarily drain gabbro, but some tributaries access limestone and volcanogenic sediments. The goal of the study was to understand controls on riverine δ 88/86 Sr values in a landscape with multiple factors that may influence chemical weathering, including dense vegetation, high rainfall, and abundant, freshly-eroded Holocene fluvio-glacial and landslide debris. Rivers draining gabbro have higher δ 88/86 Sr values than bedrock, by as much as ∼0.14‰, and the δ 88/86 Sr values strongly correlate with molar Ca/Sr ratios ( R 2  = 0.69). Leaching of rocks and sediment reveals no evidence for the preferential dissolution of minerals having high δ 88/86 Sr values and Ca/Sr ratios. In-stream Sr isotope fractionation seems unlikely because comparison against 87 Sr/ 86 Sr and Ca/Sr ratios demonstrates that riverine δ 88/86 Sr values conservatively trace water-mass mixing. The riverine data are best explained by the input of soil water, which is distinct from potential bedrock end-members (i.e., silicates and carbonates) based on δ 88/86 Sr but indistinguishable in terms of Ca/Sr and 87 Sr/ 86 Sr. While strontium isotope fractionation during secondary mineral formation and pedogenesis is possible, clay mineral formation is minor and most soils are poorly developed. Instead, soil water δ 88/86 Sr values more likely reflect plant uptake. Plant samples yielded a wide range of δ 88/86 Sr values, but on average, they are lower than those for bedrock, consistent with the expectation that plants preferentially incorporate lighter Sr isotopes. Mass-balance constraints, together with 87 Sr/ 86 Sr ratios, indicate that soil water δ 88/86 Sr values are ∼0.30‰ higher than bedrock δ 88/86 Sr values, and mixing calculations show that the plant-fractionated soil water pool contributes ∼27% of the riverine Sr. For tributaries accessing limestone and volcanogenic sediments, Ca/Sr and 87 Sr/ 86 Sr ratios appear consistent with two-component mixing between silicate and carbonate weathering, but δ 88/86 Sr values reveal a third contribution from soil water inputs, similar to gabbro catchments. The results of this study suggest that Sr isotopes behave conservatively during water mass mixing and stream transport but non-conservatively in soil, where plant uptake can elevate soil water δ 88/86 Sr values relative to bedrock. Plant uptake, or related biogeochemical processes, such as ion-exchange on organic matter surfaces, also appear to modify soil water Ca/Sr ratios. Many studies use 87 Sr/ 86 Sr and Ca/Sr ratios to apportion riverine solutes between silicate and carbonate weathering, but Ca/Sr ratios may be non-conservative in densely vegetated areas. The stable Sr isotope tracer shows promise for resolving riverine cation sources, as well as effects from biological cycling.